Provisional Volume Tables for Two Exotic Pines (species Pinus caribaea and Pinus patula) - Singh, S. P.; Mittal, M. C. (Indian Forester, 1982)
Provisional volume tables for Pinus caribaea and Pinus patula have been prepared. Use has been made of 'Cosh function' as independent variable to improve volume (V) prediction by V=a+b D2H regression over entire data range, where D Is diameter at breast height and H Is height of a tree.